Sensory disorder of the chest as presenting symptom of lung cancer. Issue 9 (September 1993) - Marangoni, C; Lacerenza, M; Formaglio, F; Smirne, S; Marchettini, P
Abstract : Four patients with pancoast's syndrome had burning pain in the axilla and abnormal sensation in the intercostobrachial nerve territory. The intercostobrachial nerve is the first component of the brachial plexus to be invaded by lung tumours.